2013
DOI: 10.1111/all.12131
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose aspirin desensitization in individuals with aspirin‐exacerbated respiratory disease

Abstract: Aspirin desensitization with a maintenance dose of 100 mg daily has a positive impact on nasal polyp relapse and seems to be a safe and suitable therapy to improve clinical complaints and the quality of life of individuals with AERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
1
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 28 publications
4
88
1
8
Order By: Relevance
“…This low-dose protocol was revealed to be safe, with less than 3% of patients in the treatment group complaining about gastric irritations, all of which could continue the treatment after adding a PPI. 1061 With this unprecedented LOE it was shown that 100 mg as a maintenance dose could significantly reduce the clinical key symptoms such as nasal obstruction, discharge, and headache (p = 0.001). QoL was also significantly improved over a 3-year follow-up period in the treatment group (p = 0.03), along with a lower polyp score after 36 months.…”
Section: Viiie10 Crswnp and Aerd Managementmentioning
confidence: 99%
“…This low-dose protocol was revealed to be safe, with less than 3% of patients in the treatment group complaining about gastric irritations, all of which could continue the treatment after adding a PPI. 1061 With this unprecedented LOE it was shown that 100 mg as a maintenance dose could significantly reduce the clinical key symptoms such as nasal obstruction, discharge, and headache (p = 0.001). QoL was also significantly improved over a 3-year follow-up period in the treatment group (p = 0.03), along with a lower polyp score after 36 months.…”
Section: Viiie10 Crswnp and Aerd Managementmentioning
confidence: 99%
“…The clinical symptoms of urticaria or anaphylaxis usually appear at standard to high doses, which is an important distinction to sensitized individuals having IgE reactions. The dose dependence is also well documented by successful desensitization procedures in various pseudo-allergic reactions [54,55]. In NSAID-related pseudo-allergy, the underlying inflammation and effector cell hyperreactivity influences the clinical severity [56].…”
Section: Relation Of Allergic-immune P-i and Pseudo-allergic Reactimentioning
confidence: 99%
“…26 Furthermore, patients with AERD can be successfully desensitized with as little as 81 mg of aspirin per day. 27,28 The aim of the present study was to explore the possible role of platelets in the pathogenesis of AERD under stable conditions. Furthermore, we also assessed platelet activation markers in plasma during an aspirin challenge test.…”
mentioning
confidence: 99%